2013
DOI: 10.1590/s0073-47212013000300008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental factors on community structure of Leptophlebiidae (Insecta, Ephemeroptera) in Cerrado streams, Brazil

Abstract: ABSTRACT. We analyzed the effects of environmental factors on abundance, species richness, and functional group richness of Leptophlebiidae in 16 sampling points along four Cerrado streams. Across three periods of 2005, we collected 5,492 larvae from 14 species in stream bed substrate. These species belong to three functional feeding groups: scrapers, filtering collectors and shredders. The abundance and species richness were not affected by water quality, but habitat quality related to presence of riparian ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 24 publications
0
12
0
2
Order By: Relevance
“…Dias-Silva et al (2010) found a reduction in the species richness of Gerromorpha (Heteroptera) with decreasing habitat integrity, for example, while Silva-Pinto et al (2012), detected morphometric asymmetries in odonates. Pereira et al (2012) recorded alterations in the species composition of an assemblage of Trichoptera, while Carvalho et al (2013) observed a shift in the species richness of odonates, and Brasil et al (2013) recorded a reduction in the abundance of shredder leptophlebiids. Leptoblebiids have also been shown to be good indicators in other parts of the world.…”
Section: Effects Of the Environmental Gradientmentioning
confidence: 99%
See 4 more Smart Citations
“…Dias-Silva et al (2010) found a reduction in the species richness of Gerromorpha (Heteroptera) with decreasing habitat integrity, for example, while Silva-Pinto et al (2012), detected morphometric asymmetries in odonates. Pereira et al (2012) recorded alterations in the species composition of an assemblage of Trichoptera, while Carvalho et al (2013) observed a shift in the species richness of odonates, and Brasil et al (2013) recorded a reduction in the abundance of shredder leptophlebiids. Leptoblebiids have also been shown to be good indicators in other parts of the world.…”
Section: Effects Of the Environmental Gradientmentioning
confidence: 99%
“…The final index varies from zero to one, with the highest scores referring to the most intact environments. The index has been used in a number of studies of environmental impact, and has produced good results for the analysis of the communities of a number of taxonomic groups of aquatic insects across different regions (e.g., Dias-Silva et al, 2010;Silva et al, 2010;Souza et al, 2011;Pereira et al, 2012;Silva-Pinto et al, 2012;Brasil et al, 2013;Carvalho et al, 2013).…”
Section: Collection Of Environmental Datamentioning
confidence: 99%
See 3 more Smart Citations